2015
DOI: 10.1002/nbm.3253
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantitative magnetization transfer imaging correlates with histology during de‐ and remyelination in cuprizone‐treated mice

Abstract: The pool size ratio measured by quantitative magnetization transfer MRI is hypothesized to closely reflect myelin density, but their relationship has so far been confirmed mostly in ex vivo conditions. We investigate the correspondence between this parameter measured in vivo at 7.0 T, with Black Gold II staining for myelin fibres, and with myelin basic protein and beta-tubulin immunofluorescence in a hybrid longitudinal study of C57BL/6 and SJL/J mice treated with cuprizone, a neurotoxicant causing relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 38 publications
3
76
0
1
Order By: Relevance
“…A recent study of demyelination by induction of experimental autoimmune encephalomyelitis in mice even found that changes in MTR did not correlate with myelin content, questioning the usefulness of MTR as a surrogate marker for demyelination in that mouse model (Fjaer et al, 2015). Quantitative magnetization transfer studies reported a strong correlation between the measured bound pool fraction F and the myelin fraction, with potentially improved specificity (Thiessen et al, 2013; Turati et al, 2015). However, while providing useful information on the overall myelin content, magnetization transfer-based techniques, as T 2 based techniques, are less sensitive to the functional integrity of the myelin as might be reflected by sheath thickness, or the differentiation between intact myelin and debris.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of demyelination by induction of experimental autoimmune encephalomyelitis in mice even found that changes in MTR did not correlate with myelin content, questioning the usefulness of MTR as a surrogate marker for demyelination in that mouse model (Fjaer et al, 2015). Quantitative magnetization transfer studies reported a strong correlation between the measured bound pool fraction F and the myelin fraction, with potentially improved specificity (Thiessen et al, 2013; Turati et al, 2015). However, while providing useful information on the overall myelin content, magnetization transfer-based techniques, as T 2 based techniques, are less sensitive to the functional integrity of the myelin as might be reflected by sheath thickness, or the differentiation between intact myelin and debris.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, differences in MT measures strongly correlate with myelin content in both white (Mottershead et al, 2003, Schmierer et al, 2007, Turati et al, 2015) and gray matter (Fjær et al, 2013). While myelin is also a significant determinant of R 1 (Gouw et al, 2008, Koenig, 1991, Mottershead et al, 2003), other features of the myeloarchitecture such as the axonal diameter, perhaps coupled to the exposed myelin surface, may be a greater determinant, at least in white matter (Harkins et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both methods suffer from some limitations and any error to the parametric maps derived from them will of course propagate into the g-ratio. While F has been shown to correlate with myelination (e.g., [Turati et al., 2015]), MT is also sensitive to other factors, such as edema, inflammation, and pH (Stanisz et al., 2004, Vavasour et al., 2011). NODDI enables the estimation of v ic and v iso using clinically feasible acquisition protocols; however, this comes at the price of making some strong assumption about the intracellular diffusivity (Zhang et al., 2012).…”
Section: Discussionmentioning
confidence: 99%